ANALYSIS OF METHODS OF ENSURING PORT SECURITY IN SWITCHES - Rajabboyeva Surayyo Baxrom qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract — This article analyzes how to enable port security on the switch, how to prevent port security violations, and how to protect against attacks. Switches are basic network devices that are mainly responsible for forwarding packets from one port to another. Although they are busy performing this important function, modern switches are capable of inspecting packet headers to enforce security policies at the network level. Port security is a network security feature that operates at layer 2 of the OSI model. It is mainly used to control and restrict access to the Ethernet ports of the switch. By implementing port security, network administrators can allow only authorized devices to connect to specific switch ports. Today, port security is an important aspect of network infrastructure, not only focused on port protection, but also used to enhance features such as PortFast and Bridge Protocol Data Unit (BPDU) protection, Loop Prevention, DHCP Snooping and MAC filtering.